2020
DOI: 10.1007/s40201-019-00440-4
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of oil spill from sea water surface using magnetic wood sawdust as a novel nano-composite synthesized via microwave approach

Abstract: Water pollution by oil is a serious environmental problem. Developing new generation of benign adsorbents satisfying several criteria required for real practical application is of great need. This work introduces an effort in this direction, by utilizing a facile synthesis of wood sawdust coated magnetite nanoparticles functionalized stearic acid (WSD@Fe 3 O 4 NPs/SA) as a novel nano composite along with its precursor WSD@Fe 3 O 4 NPs. SA was covalently bonded to the precursor by amide bond formation via the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Thus, water molecules loaded with dye could be bonded onto the composite, and then, the dye molecules are exchangeable. The significance of cellulosic composite in improving the adsorption uptake is in accordance with previous reports investigated by Shaheen and Emam (2018) and Soliman et al (2020).…”
Section: Synozol Red K-hl Sorption Related To Contact Timesupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, water molecules loaded with dye could be bonded onto the composite, and then, the dye molecules are exchangeable. The significance of cellulosic composite in improving the adsorption uptake is in accordance with previous reports investigated by Shaheen and Emam (2018) and Soliman et al (2020).…”
Section: Synozol Red K-hl Sorption Related To Contact Timesupporting
confidence: 92%
“…Fe 3 O 4 nanoparticles were mixed with the cellulosicbased SWD prepared material in various wt% proportions from the blend of SWD/magnetite in a proportion marked as SF-1:1, SF-2:1, SF-3:1, SF-5:1 and SF-1:2. Afterwards, the prepared mixture are grinded by mortar of agate then retained in a glass petri dish where it is wetted with drops of distilled water prior to exposed to domestic microwave oven (5 min, 200 watts) to attain a homogeneous brownish colour composite as previously detailed in the literature (Soliman et al 2020). The graphical illustration of the preparation and treatment steps is given in the schematic of Fig.…”
Section: Preparation Of Sawdust/magnetite Sf-materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethane resins modified with magnetic particles, on the other hand, can remove 10 g of oil from the water per gram of the composite [ 41 ]. Another composite prepared with magnetic wood sawdust presented an oil removal efficiency of 28 g/g [ 42 ]. In turn, a magnetic nanostructured graphene composite was produced for oil removal, and the results showed that the oil removal capability was equal to 53 g/g [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al ( 2020 ) also reported the ability of magnetic graphene oxide composites to serve as demulsifiers in crude oil removal. Wood sawdust-coated magnetite nanoparticles functionalized with stearic acid were demonstrated to effectively remove oil from seawater by adsorption (Soliman et al 2020 ), while Kamgar et al ( 2020 ) functionalized sawdust with Iron oxide nanoparticles also recorded efficient crude oil removal from aqueous solution.…”
Section: Existing and Emerging Remediation Approach For Crude Oil Pollutionmentioning
confidence: 99%